The Role of Limit Pricing in Sequential Entry Models - Jeffrey Church; Roger Ware (Queen's University, Department of Economics, 1991)
In this paper we establish a complete characterization of the strategic interaction of firms in sequential entry models. The limit price plays an important coordinating role in non-cooperative sequential entry models. We show that for many firms in a large range of sequential entry equilibria, the limit price is effectively parametric, so that firms make investment decisions in a quasi-competitive manner. Entry deterrence is only pursued by firms at the beginning of the sequence if it is profitable; otherwise it is delegated to the last firms to enter.
Keywords: 330